2019
DOI: 10.3802/jgo.2019.30.e5
|View full text |Cite
|
Sign up to set email alerts
|

Association of pretreatment thrombocytosis with prognosis in ovarian cancer: a systematic review and meta-analysis

Abstract: ObjectiveTo investigate the association between pre-treatment thrombocytosis and prognosis in patients with ovarian cancer (OC).MethodsPubMed, EMBASE, and the Cochrane Library were searched for articles regarding the prognosis of OC patients with pre-treatment thrombocytosis by the end of March 2018. Pooled estimates for overall survival (OS) and progression-free survival (PFS) events were calculated as hazard ratios (HRs) either on a fixed or random effect model by Stata 13.0 software. Funnel plot and Egger's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
2
17
1
Order By: Relevance
“…These findings were also confirmed in a recent systematic review and meta-analysis of 11 pooled studies conducted by Ye et al . [ 21 ] reported that pretreatment thrombocytosis was a significant negative predictor of both PFS and OS in women with EOC for all stages and degrees of differentiation. This is at variance to the work of Allensworth et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were also confirmed in a recent systematic review and meta-analysis of 11 pooled studies conducted by Ye et al . [ 21 ] reported that pretreatment thrombocytosis was a significant negative predictor of both PFS and OS in women with EOC for all stages and degrees of differentiation. This is at variance to the work of Allensworth et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] A recent systematic review and meta-analysis conducted by Ye et al reported that pretreatment thrombocytosis was a significant negative predictor of both survival in women with epithelial ovarian cancer (EOC). [ 21 ] However, it is still not clearly understood whether prognosis in ovarian cancer patients is directly affected by the presence of a high level of platelets or if thrombocytosis is a surrogate for other prognostic indicators, such as advanced-stage disease, suboptimal cytoreduction, or even medical comorbidity. On this basis, the current study, therefore, investigated the impact of pretreatment thrombocytosis on progression-free survival (PFS) and overall survival (OS) in black Nigerian women with EOC.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researches showed that platelet activation play an important part in cancer progression. Thrombocytosis is related to worse clinical outcome in patients with various cancers, including ovarian cancer, colorectal cancer, and pancreatic cancer 2022 . The PDW that is one of the platelet indices not merely check platelet volume heterogeneity, but also reactive platelet activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytosis observed in oncology patients has been reported to entail a worse prognosis in a variety of solid tumours: colorectal, 6 , 7 breast, 8 lung, 6 , 9 renal, 6 , 10 cervical, 11 ovarian 12 and brain tumours. 13 Only meagre data are available in the literature on the relationship between thrombocytosis and prostate cancer.…”
Section: Introductionmentioning
confidence: 99%